SOSIALISASI BETON FEROSEMEN DENGAN KETERLIBATAN P3A UNTUK PERBAIKAN JARINGAN IRIGASI DI D.I COMAL - Ingerawi Sekaring Bumi; Wildan Herwindo; Tia Hetwisari; Didit Puji Riyanto; Yanida Agustina; Widiawati Widiawati; Nerisa Shivanadya (Jurnal Pengabdian kepada Masyarakat, 2024)
One of the irrigation areas in Central Java Province is the Comal Irrigation Area (D.I Comal) which is included in the Comal Watershed (DAS). D.I Comal has an area of 8946.79 Ha. The current condition of the Comal irrigation area is experiencing damage to several parts of the canal. This can cause water loss/leakage thereby reducing irrigation efficiency and effectiveness. This problem is being addressed by the Water Users Farmers Association (P3A) independently. The development of irrigation modernization goes up with the expansion of various alternative materials for irrigation channels, including ferrocement. Ferrocement is a mortar made from a homogeneous mixture of sand, cement, water and reinforced with reinforcement coated with woven wire (galvanized) with thickness of 3 to 6 cm. The Public Works Polytechnic provides community service by building a pilot irrigation repair using ferrocement concrete. The project are rehabilitation of tertiary channels and distribution boxes. This community service is in collaboration with P3A D.I Comal and the Irrigation Engineering Center. Outreach activities were also carried out to the public. It is hoped that the inclusion of PU Polytechnic in the community will provide benefits to the society in improving the quality of the irrigation network in D.I Comal.